MICRONUTRIENT THERAPY FOR SEPSIS - Prasetiyo, Agung; Nasronudin, Nasronudin (Indonesian Journal of Tropical and Infectious Disease, 2015)
Micronutrients are nutrients which are needed by the body to perform the function of body. The amounts is less than 100% Î¼g per day and consist of vitamins and minerals. It cannot be synthesized in the body. Research in the US mentioned that the rate prevalence of sepsis is tended to be increased 8.7 % annually. In sepsis, nutrition is one of the important component which could drive the success treatment. Micronutrient, especially a vitamin which is soluble in fats, it would be toxic if the number exceed the capability of body to receive it. Although there are guidance and mutual agreement about sepsis using, it still need to concern on micronutrient which potentially giving bad effect. In sepsis case, micronutrients also determine the success of treatment due to redistribution of vitamin and trace element from circulation to the tissue which involved in the proteins formation and immune system. The conclusions of the latest 7 experiments and 4 random controlled studies of multi-centre support the micronutrients supplementation because it can decrease mortality rate. However, it still need to be aware to the toxicity of fat soluble micronutrient if the doses are excessive.